Penerapan Etika Bisnis Berdasarkan Hukum Islam pada Transaksi Jual Beli di Pasar Tradisional - Sunaria Kaisupy; Hasan Hasan; Evy Savitri Gani (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of the study was to determine the application of business ethics based on Islamic law to the practice of buying and selling in traditional markets. This type of research uses a qualitative approach. The subjects in this study were traders who made buying and selling transactions in the traditional market of Hamlet Olas. The technique of determining the subject by purposive sampling is the determination of the subject using criteria for the type of goods sold. The results of research in the traditional market of Olas Hamlet obtained, the practice of buying and selling transactions was found by traders who prioritized profit even though the quality of the goods they sold was not appropriate. The practice of buying and selling transactions carried out by traders has not fully implemented ethical principles that are in accordance with Islamic business. In addition, it is the lack of friendliness of the merchants that makes buyers uncomfortable. When viewed from the five principles of Islamic business ethics, namely the principle of unity, the principle of balance and freedom have been well applied by traders. However, it can be seen from the principle of responsibility and the principle of righteousness, virtue and honesty have not been fully carried out by traders and are more concerned with profit alone